Determination Of Acoustic Properties Of Rice Bran Composites A Material Handler Noise - Rafika Andari (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2018)
The examination of the acoustic characteristic of rice bran has been performed. The materials are the alternative materials of the noise controllerfrom the use of synthetic fiber materials like glasswool. The examination is completed by using tube impedance method. The result of the examination reveals that the natural fiber materials that have been mixed with glue have a good value of sound absorption at frequency 400-1200 Hz whereas at frequency 200 Hz, its value does not change significantly. The high value of the sound absorption is owned by materials with the bigger porous. Beside the coefficient of the absorbtion, the examination of value of acoustic impendence is also performed. The result shows that the similar composition between natural fiber and glue has a bigger value of impendence compared to the lower composition of glue. It is caused by the fulfillment of the bigger amount of the porous by glue.